Analisis Majas Dan Diksi Antologi Geguritan Kawula Mung Saderma Karya Jadid Al Farisy: Kajian Stilistka - Fauziyah, Syifa; Zaidah, Nuning; Alfiah, Alfiah (Universitas PGRI Semarang, 2025)
The use of figures of speech and diction in this anthology is also an important element that makes it a work deserving of deeper study. Figures of speech are the use of the richness of language with certain varieties to achieve effects. This study aims to describe the figures of speech and diction employed in the anthology of geguritan Kawula Mung Saderma by Jadid Al Farisy. This type of research is qualitative research. The data collection techniques used are the Listening technique and the note-taking technique. The data analysis techniques used are: data reduction, data display, and conclusion drawing/verification. The results of the study can be concluded that by studying the 6 selected geguritan, namely Jampining Ati, Sekaring Sonya, Jimat Abang Putih, Kusumaning Nagri, Lir Gumanti, Setija, from the 6 geguritan it was found that the use of figures of speech in these geguritan is diverse, including metaphor, personification, paradox and hyperbole, symbolic and repetition which strengthen the aesthetics and meaning in each verse. The diction used by the poet includes denotation, connotation, abstract words, concrete words and general words. This shows the accuracy in choosing words that reflect the depth of meaning and the strong nuances of Javanese culture. This study can be developed by analyzing other stylistic aspects, such as phonology, syntax, or discourse in Geguritan Kawula Mung Saderma.